Performance Comparison of the Driller’s Method and Wait and Weight Method for Effective Well Kick Management of Rig AAM#18 ZJ70DBS 2000 HP - Agustina Prihantini; Adrian Indarti; Mulkan Hafiz (Gema Wiralodra, 2025)
KW Well in the S Field is a development well in Bojonegoro, East Java, drilled with the AAM #18 ZJ70DBS 2000 HP rig. Drilling activities in the oil and gas sector frequently encounter risks, one of which is a well kick, defined as the entry of formation fluids into the wellbore that can escalate into a blowout. This research focuses on implementing the Wait and Weight method to manage a kick in KW Well, after the Driller’s Method had initially been applied. The Wait and Weight technique was selected because it lowers pressure at the casing shoe, completes control with a single circulation, and works well in loss-prone formations. The analysis used field data such as casing and drill string dimensions, hole size, LOT results, depth, initial mud weight, pump rate, shut-in drill pipe and casing pressures, and pit gain. The kick occurred due to hydrostatic pressure being insufficient to balance formation pressure. Using the Wait and Weight method required 3,679.84 pump strokes and 122.66 minutes of pumping. In contrast, the Driller’s Method needed 6,227.16 strokes and 3 hours 28 minutes. This comparison shows that the Wait and Weight method is more efficient in both time and pump strokes, making it a preferable option for managing kicks under similar well conditions.